KEMAMPUAN BAHAN SEDIAAN SIRUP BUAH NAGA SUPER MERAH (Hylocereus costaricensis) DALAM MENURUNKAN GLUKOSA DARAH PENDERITA DIABETES MELITUS TIPE 2 - Sasi Gendro Sari; Siti Aminah; Rusmiati Rusmiati (Universitas Lambung Mangkurat, 2024)
The research aimed to determine the effect of pitaya's pulp and its peel as syrup sources against blood glucose level in diabetes melitus patients, to examine the glicemic index value, and to compare the difference of nutrition between the two syrup sources. Pitaya was obtained from pitaya’s agriculture at Pelaihari, Tanah Laut Regency and probandus samplings were selected from ten diabetes melitus patients's list of Idaman Banjarbaru Hospital. Pitaya samples were divided into three classification such as a sample A (200 g pulp), a sample B (100 g pulp, 100 g peel, 100 mL aquadest), a sample C (200 g peel, 200 mL aquadest) and a control D as a diet indicator (100 g white bread). The syrup was given to the patients after 10 hours of their fasting, and then blood samples were taken 1-2µL from their finger tip to measure blood sugar. The result showed a significant effect of lowering blood glucose level. The glicemic index values of samples A, B, and C were 46,24%, 35,51% and 35,39% respectively and their values had low glicemic index values. Syrup samples were measured based on proximate analysis, sugar levels and antioxidant activities. The concentrations of water contents, ash contents, carbohydrate, and protein from samples A, B and C were significantly different, meanwhile antioxidant and lipid levels were not significantly different. Sugar containing in syrup samples A, B, and C were categorized at low levels as follow: 13brix, 3,8brix, and 1,2 brix respectively.